2014
DOI: 10.1016/j.jpain.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Age and Race Effects on Pain Sensitivity and Modulation Among Middle-Aged and Older Adults

Abstract: This study tested the effects of aging and race on responses to noxious stimuli using a wide range of stimulus modalities. The participants were 53 non-Hispanic Blacks and 138 non-Hispanic White adults, ages 45 to 76. The participants completed a single 3-hour sensory testing session where responses to thermal, mechanical, and cold stimuli were assessed. The results suggest that there are selected age differences, with the older group less sensitive to warm and painful heat stimuli than middle-aged participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
112
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 53 publications
(74 reference statements)
13
112
2
2
Order By: Relevance
“…This result confirms other demonstrations of an inhibitory effect of CPM on pain [14,36]. However, the reduction in pain sensitivity following CPM was comparable for younger and older subjects in the present study, whereas previous studies have described less inhibition for older subjects [4,1215] or inhibition for young and facilitation for older subjects during CPM paradigms [16,20]. An important factor in these differences may be the oscillations in stimulation intensity during long duration REDSTIM that could mask or interfere with other sources of inhibition or facilitation.…”
Section: Discussionsupporting
confidence: 92%
“…This result confirms other demonstrations of an inhibitory effect of CPM on pain [14,36]. However, the reduction in pain sensitivity following CPM was comparable for younger and older subjects in the present study, whereas previous studies have described less inhibition for older subjects [4,1215] or inhibition for young and facilitation for older subjects during CPM paradigms [16,20]. An important factor in these differences may be the oscillations in stimulation intensity during long duration REDSTIM that could mask or interfere with other sources of inhibition or facilitation.…”
Section: Discussionsupporting
confidence: 92%
“…Some research studies have revealed that pain may be less frequent and less severe in PWD suffering from some acute medical conditions (Gibson, 2015;Hadjistavropoulos et al, 2015;Pignataro & Swisher, 2010). Two recent studies (Riley et al, 2014;Stabell, Stubhaug, Flaegstad, & Nielsen, 2013) have revealed that pain threshold increases with age. However, a recent study revealed that whether there is no change or decrease in pain thresholds as age advances (Leegaard, Lomholt, Thastum, & Herlin, 2013).…”
Section: Physical Painmentioning
confidence: 99%
“…14 The threshold for pain may vary based on the type of stimulus (increase with heat, no change with electrical stimulation, decrease with mechanical pressure and ischemia), duration (increase with shorter duration), and location (increase at peripheral or visceral site). 13,15,16 Although pain may not serve as a reliable warning sign of tissue damage in some atypical clinical presentations (cardiac ischemic pain, abdominal pain) because of the increased pain threshold, this finding should not lead to the conclusion that most of the older adult population will not experience pain. 17,18 Rather, the increased pain threshold that accompanies aging may imply that more significant levels of underlying pathologic disorder may be present in older adults who endorse pain.…”
mentioning
confidence: 99%